Chemical characterization of stromatolitic "petola" layer (Sečovlje salt-pans, Slovenia) using FT-IR spectroscopy - Kovač, Nives (Annales. Series historia naturalis, 2009)
At Sečovlje salt-pans (Gulf of Trieste, northern Adriatic), the stromatolitic microbial mat named "petola" is crucial element in old mediaeval manner of salt-production, so the understanding of its chemistry is highly significant for the preservation and progress of this activity. The infrared spectra (FT-IR) of homogenized bulk samples were recorded to investigate the petola composition and modifications...
Keywords: FTIR spektroskopija; petola; Sečoveljske soline; Sečovlje Saltworks; stromatolit